2020
DOI: 10.1089/fpd.2019.2703
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Antimicrobial Resistance Profiles of Campylobacter jejuni, Campylobacter coli, and Campylobacter upsaliensis in Beef Cattle on Cow–Calf Operations in South Africa

Abstract: This study investigated occurrence and antimicrobial resistance profiles of Campylobacter spp. isolates in beef cattle on five cow-calf operations in South Africa. A total of 537 fecal samples from adult beef cattle (n = 435) and rectal swabs from calves (n = 102) were screened for Campylobacter jejuni, Campylobacter coli, and Campylobacter upsaliensis by culture and polymerase chain reaction. Furthermore, 86 Campylobacter spp. isolates including 46 C. jejuni,24 C. coli, and 16 C. upsaliensis were tested for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
7
7
0
Order By: Relevance
“…However, the finding of this study is consistent with a similar study conducted in diarrheal patients in Fin-land [50]. However, antimicrobial resistance was documented as 46.7%, 35.6%, and 17.8% in C. jejuni, C. coli, and C. upsaliensis isolates, respectively, in beef cattle of South Africa [51]. Conversely, higher levels of resistance to ciprofloxacin and tetracycline as >80% and> 70%, respectively, were captured in the diarrheal sample in the Arabian Gulf region [52].…”
Section: Discussionsupporting
confidence: 91%
“…However, the finding of this study is consistent with a similar study conducted in diarrheal patients in Fin-land [50]. However, antimicrobial resistance was documented as 46.7%, 35.6%, and 17.8% in C. jejuni, C. coli, and C. upsaliensis isolates, respectively, in beef cattle of South Africa [51]. Conversely, higher levels of resistance to ciprofloxacin and tetracycline as >80% and> 70%, respectively, were captured in the diarrheal sample in the Arabian Gulf region [52].…”
Section: Discussionsupporting
confidence: 91%
“…The numbers on the branches present the difference degree in allelic profiles for housekeeping genes. Kang et al, 2006;Little et al, 2008;Torralbo et al, 2015;Tang et al, 2017;Guk et al, 2019;Karama et al, 2020). This was similar to the results of a previous study reporting a high prevalence (56-77%) of C. coli in swine colon samples (Kempf et al, 2017), indicating that pigs are a major reservoir of C. coli.…”
Section: Discussionsupporting
confidence: 90%
“…We identified that the majority of swine fecal samples were positive for C. coli (66.3%, 124/187, 95% CI 52.9–80.8%). The prevalence of C. coli in pigs in this study was higher than that in other livestock, including cattle (7.4–15.0%) and poultry, such as chickens (26.4–40.2%) and ducks (46.6–57.9%) ( Bae et al, 2005 ; Kang et al, 2006 ; Little et al, 2008 ; Torralbo et al, 2015 ; Tang et al, 2017 ; Guk et al, 2019 ; Karama et al, 2020 ). This was similar to the results of a previous study reporting a high prevalence (56–77%) of C. coli in swine colon samples ( Kempf et al, 2017 ), indicating that pigs are a major reservoir of C. coli .…”
Section: Discussionmentioning
confidence: 51%
“…Our results show that erythromycin was the second most efficient antibiotic in the evaluated strains, with a percentage of 34.3% (12/35) of resistance. Despite this, studies show an even greater efficiency with resistance rates ranging from 0 to 17.4% in several countries ( Aksomaitiene et al., 2019 ; Melo et al., 2019 ; Otto et al., 2019 ; Tryjanowski et al., 2019 ; Elhadidy et al., 2020 ; Karama et al., 2020 ). In a contradictory way, it is possible to find high levels of resistance in isolated strains of chickens ( Asuming-Bediako et al., 2019 ; Pillay et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%